The law and disability discrimination in Nigeria (2008)
This study has examined the incidence of disability as a human experience that attracts discrimination and particularly in Nigeria as a developing country. It has found discrimination to be expressed in terms of the names disabled persons are called' the causes adduced for disability under customary law and discriminatory practices under customary law. These practices include deification, mutilation and scarification. It also includes giving of care motivated by wrong motives, using a person with a disability to apply pressure on a debtor to make him pay, occupational biases, institutionalization and many other discriminatory practices. The work is in three main parts namely the pre-missionary, the missionary and the post missionary eras. The importance of legislations in regulating the relationship of society with people who have disability is examined and some recommendations are made for better protection for persons with disabilities and then a conclusion.